A prospective investigation of dietary patterns and internalizing and externalizing mental health problems in adolescents - Trapp, Georgina; Allen, Karina; Black, Lucinda; Ambrosini, Gina; Jacoby, Peter; Byrne, Susan; Martin, Karen; Oddy, Wendy (2016)
© 2016 The Authors. Food Science & Nutrition published by Wiley Periodicals, Inc.Investigating protective and risk factors that influence mental health in young people is a high priority. While previous cross-sectional studies have reported associations between diet and mental health among adolescents, few prospective studies exist. The aim of this study was to examine prospective relationships between dietary patterns and mental health among adolescents participating in the Western Australian Pregnancy Cohort (Raine) Study. Self-report questionnaires were used to assess indicators of mental health (Youth Self-Report externalizing/internalizing T-scores) and Western and Healthy dietary patterns (identified using factor analysis) at 14 (2003–2005) and 17 years (2006–2008). Multivariate linear and logistic regression were used to assess relationships between dietary patterns and mental health. Complete data were available for 746 adolescents. In females only, the Western dietary pattern z–score at 14 years was positively associated with greater externalizing behaviors at 17 years (ß = 1.91; 95% CI: 0.04, 3.78) and a greater odds of having clinically concerning externalizing behaviors at 17 years (OR = 1.90; 95% CI: 1.06, 3.41). No other statistically significant associations were observed. Overall our findings only lend partial support to a link between diet and mental health. We found it to be specific to females consuming a Western dietary pattern and to externalizing behaviors. Future research on dietary patterns and mental health needs to consider possible sex differences and distinguish between different mental health outcomes as well as between healthy and unhealthy dietary patterns.